Variação interanual da comunidade fitoplanctônica em ambientes da planície de inundação do alto rio Paraná : influência do regime hidrossedimentológico. - Rodrigues, Luzia Cleide (2007)
This study investigated the central paradigm that the natural hydrosedimentological regime of Paraná River, acts as a structuring factor of biotic and abiotic components from Upper Paraná River floodplain. Therefore, we evaluated sets of interannual data of phytoplankton community in environments from this floodplain. Species richness, density and biovolume of phytoplankton were analyzed during a period before the building of Porto Primavera Power Plant and during the following 6 year after the reservoir impoundment (2000-2005). Multiple regression analyses were accomplished to test the differences between periods and to find predictor variables of phytoplankton structure of studied environments. This study was divided into two chapters, the first, entitled "Interannual variability of phytoplankton from Upper Paraná River floodplain (Porto Rico-PR): Influence of hydrosedimentological regime and the construction of Porto Primavera dam", in which phytoplankton changes in Paraná River were verified, in function of the formation of Porto Primavera Reservoir and the climatic alterations that occurred during the period studied (1993-1994 and 2000-2005), especially those related to El Niño and La Niña phenomena. In the second chapter entitled "Interannual variation of phytoplankton in a river-flooding lake system (Upper Paraná River, Brazil)", we verified that the alterations of phytoplankton structure in Patos Lagoon and Ivinhema and Paraná rivers were associated to the fluctuations of hydrosedimentological regime of Ivinhema and Paraná rivers, probably, influenced by the phases La Niña (2000-2001) and El Niño (2003-2004) Southern Oscillation cycle (ENSO).